Political Rhetoric of Jokowi and Prabowo in the 2019 Presidential Election: A Semiotic Analysis of Tempo Magazine Covers - Triyono Lukmantoro; Nurul Hasfi; Tandiyo Pradekso; Sandy Allifiansyah (Ikatan Sarjana Komunikasi Indonesia, 2025)
Tempo magazine's covers depicting the political battle between Jokowi and Prabowo in the context of the 2019 Presidential Election are worth examining. Not only because in 2019, Jokowi and Prabowo met as rivals who defeated each other for the second time after the 2014 Presidential Election. Using semiotic analysis and media agenda setting theory, this study aims to identify the connotational aspects of the figures of Jokowi and Prabowo in the context of the 2019 Presidential Election on various covers of Tempo magazine. This research highlights the importance of the agenda setting process carried out by the Tempo Magazine Editor in determining the cover of Tempo Magazine in the context of the 2019 presidential election in Indonesia. This study finds that Tempo Magazine’s covers show no bias toward any presidential candidate, positioning Tempo as a neutral observer of the candidates' political behavior. The covers depict a balance of power leading to societal polarization and support divisions. Moreover, the agenda media discourse shows, instead of building opposition, it suggests a political coalition, reflecting the political communication character of Jokowi administration.